Technical Competence Of Madrasah Administrative Personnel In Managing Web-Based Information Systems - Abdul Rahman Aulia; Irawati Irawati; Rini Setyaningsih (At-Tarbiyat, 2023)
This research aimed at finding out how administration staff did their technical competences in managing web-based information systems at State Islamic Senior High School 3 Pekanbaru. The foci of this research were 1) “how was the management of web-based information systems at State Islamic Senior High School 3 Pekanbaru?”, and 2) “how was the implementation of the technical competences of administration staff in managing web-based information systems at State Islamic Senior High School 3 Pekanbaru?”. It was qualitative descriptive research. Interview, observation, and documentation were the techniques of collecting data. The data in this research were analyzed with the steps—data collection, data reduction, data display, drawing conclusions, and verification. The object was the technical competences of administration staff in managing web-based information systems at State Islamic Senior High School 3 Pekanbaru. The subjects of this research were administration staff at State Islamic Senior High School 3 Pekanbaru. The informants in this research were the head of administration staff and 1 administration staff in the computer data center field as the main informants. The research findings indicated that, web-based information system management was carried out by system planning, system design, system implementation, system control, and system maintenance. In the management of web-based information systems at State Islamic Senior High School 3 Pekanbaru, administration staff carried out their technical competencies—working based on the task field of computer data center, and being skilled in using hardware and web-based information system software. Based on the findings obtained, it was necessary to improve work procedures, it could be with the existence of a clear standard operational procedure, in term of managing web-based information in Islamic schools. To the government, the ministry of religion in the field of Islamic school education and staff was necessary to consider the simplification of the web-based information service system based on the functions and objectives of the information system implemented for efficiency and benefit of technology in educational administration.